ABOUT THE OF ETHONYMS ARE LEARNS ETNOTOPONYMS (EXAMPLE OF KHALAJ ETNONYMS) - Zarina, Ruzimurodova; Nematovich, Nematov Ozodbek; Yusupovna, Kushbakova Maftuna (International Journal of Psychosocial Rehabilitation, 2020)
In scientific toponymic literature, the name of ethnicity (seed, tribe, nation,) is ethnonym (Greek, ethnos - "people", onym - "name"), and any geographic object on which it is based is called ethnotoponim. Ethnotoponyms form a separate layer within the place names. Ethnic units are so old that their research is more complex and requires sufficient expertise and experience from the researcher. Most importantly, if an ethnonym is properly interpreted, the researcher can have a wealth of information about the historical formation, development, language, customs, integration, migration of an ethnos. Consequently, ethnons are the subject of research not only in toponymics but also in the disciplines such as ethnography, history, linguistics.